Chewing side preference in children with cleft palate: concordance of three methods - López-Soto, Olga Patricia; López-Soto, Lina María; Osorio-Forero, Alejandro; Restrepo-de Mejía, Francia (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the objective was to measure the concordance of three methods to determine chewing side preference in children with cleft palate. Materials and methods: The sample included 47 children with cleft palate and similar age and socioeconomic level. Methods: the test of Christensen & Radue (1985), the test of Paphangkorakit et al (2006) and surface electromyography (sEMG) were used. Comparisons among groups were made by non-parametric methods. Results: the method of Paphangkorakit et al (2006) did not show concordance with the preference measured by the Christensen & Radue method (1985) (Pearson’s χ2 = 0.96, p = 0,619; Kappa = ‒0.08, p = 0,475). The results showed that cleft type is not associated to chewing side preference measured by the method of Paphangkorakit et al (2006) (Pearson’s χ2 = 5.07; p = 0,281; Kappa = 0.07, p = 0,274) but by the method of Christensen & Radue (1985) (Pearson’s χ2 = 7.09; p = 0.029; weak Cramer’s V association = 0.39, p = 0.029; Kappa = 0.19, p = 0.009). Patients with right cleft palate differ from patients with bilateral cleft in terms of sEMG amplitude asymmetry while chewing (right: 7.3 ± 12.8; bilateral: ‒2.67 ± 6.61; U = 104; p = 0,038). Conclusion: no concordance was found between the two studied clinical methods to identify masticatory preference, nor between these and sEMG.